2008
DOI: 10.1002/ana.21483
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative magnetic resonance imaging analyses and clinical significance of hyperintense white matter lesions in systemic lupus erythematosus patients

Abstract: Small hyperintense WM lesions in SLE are associated with central nervous system symptoms and antiphospholipid antibodies, and progress over time in patients with more severe SLE. Therefore, in the context of SLE, these lesions are likely consequences of central nervous system damage and not mere incidental finding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
88
3
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(118 citation statements)
references
References 61 publications
12
88
3
2
Order By: Relevance
“…33,34 Numerous studies have also revealed WM abnormalities in patients with NPSLE, 35,36 including the presence of WM lesions 37 and increased WM tract diffusivity. 38 The pathogenesis of CNS involvement in SLE is likely related to an inflammatory response secondary to auto-antibody-mediated vasculitis.…”
Section: Discussionmentioning
confidence: 99%
“…33,34 Numerous studies have also revealed WM abnormalities in patients with NPSLE, 35,36 including the presence of WM lesions 37 and increased WM tract diffusivity. 38 The pathogenesis of CNS involvement in SLE is likely related to an inflammatory response secondary to auto-antibody-mediated vasculitis.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study in patients with newly diagnosed SLE, WMH were found in 8% of the patients 38 . Nevertheless, these lesions were observed more frequently in NPSLE when compared with SLE without neuropsychiatric manifestations, with average ranges from 40 to 60% 8, 11, 19, 34, 36, 38, 39 . WMH were associated with cerebrovascular disease, cognitive dysfunction, seizures, antiphospholipid antibodies, low complements (C3, C4, CH50), age, disease duration, and total corticosteroid dose 8, 34 .…”
Section: Introductionmentioning
confidence: 94%
“…Nevertheless, these lesions were observed more frequently in NPSLE when compared with SLE without neuropsychiatric manifestations, with average ranges from 40 to 60% 8, 11, 19, 34, 36, 38, 39 . WMH were associated with cerebrovascular disease, cognitive dysfunction, seizures, antiphospholipid antibodies, low complements (C3, C4, CH50), age, disease duration, and total corticosteroid dose 8, 34 . Previous reports demonstrated a significant association between both NPSLE activity (Neuro-SLEDAI) and injury (Neuro-SLICC) scores with the number of WMH (high lesion burden) 11, 34, 36, 38, 40 .…”
Section: Introductionmentioning
confidence: 94%
“…There is evidence that the seizures occur in the setting of brain lesions and damage to subcortical white matter following vasculitic, inflammatory, or ischemic brain injury. [56] Besides, the underlying systemic inflammatory cascades may be sufficient to cause seizures, [57] or specific antibodies to neuronal antigens may trigger seizures in some patients, although the evidence is inconclusive. [58] The development and progression of a small vessel, inflammatory vasculopathy is a hallmark of so-called ''lupus cerebritis'' or ''lupus vasculopathy. ''…”
Section: Systemic Lupus Erythematosusmentioning
confidence: 99%